IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL IN LEARNING THE HISTORY OF THE ENTRY OF HINDU-BUDDHIST RELIGION IN INDONESIA CLASS X AT SMA KEMALA BHAYANGKARI 3 PORONG - Maulidia, Wahyuni; Aziz, M. Fariz Abdul; Fajriyah, Izzatul (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study examines the planning, implementation, and evaluation of the Discovery learning model in teaching the history of the entry of Hindu-Buddhist religions into Indonesia for class X at SMA Kemala Bhayangkari 3 Porong. This research uses a descriptive qualitative approach.The data were collected through structured interviews, participatory observation, and documentation. The research was conducted at SMA Kemala Bhayangkari 3 Porong, involving grade X-12 students and history teachers. Data sources included lesson plans (RPP) and classroom documentation. The research followed several stages: pre-fieldwork, fieldwork, data collection, and report writing, with data analysis conducted through Miles & Huberman's four-step method. This study aims to explain the planning and implementation of Discovery learning, describe its implementation, an@gmail@gmail.comd evaluate it in history learning. The findings show that the planning of Discovery learning begins with a situation analysis, followed by the setting of learning objectives and the preparation of lesson plans. The implementation is divided into three phases: introduction, core activities, and closing. Core activities involve stimulating interest, identifying problems, collecting and processing data, verifying findings, and drawing conclusions collaboratively. Despite the objective of learning history to develop critical and logical thinking, students' interest in history remains low due to the perception that the subject is boring the material is too long.Interviews revealed that students find history lessons boring and prefer interactive methods such as games or quizzes. This research suggests that although Discovery learning has potential, its effectiveness depends on student engagement and a variety of teaching methods to sustain interest and achieve educational objectives.